TMOD-19. GABRIELLA MILLER KIDS FIRST DATA RESOURCE CENTER: LARGE-SCALE HARMONIZED CLINICAL AND GENOMIC DATA PLATFORM TO SUPPORT CHILDHOOD CANCER AND STRUCTURAL BIRTH DEFECT RESEARCH. (23rd April 2019) - Heath, Allison; Raman, Pichai; Zhu, Yuankun; Lilly, Jena; Taylor, Deanne; Storm, Phillip; Waanders, Angela; Ferretti, Vincent; Mattioni, Michele; Davis-Dusenbery, Brandi; Flamig, Zachary; Grossman, Robert; et al.
Abstract: Childhood cancers and structural birth defects share a common context of altered developmental biology, but the potential role of shared, genetic alterations and/or pathways across pediatric cancers and birth defects is not well explored. It is increasingly critical that genomic data are paired with high-quality clinical data to drive translational research by elucidating the relationship between genomic alterations, treatments, outcomes, and other phenotypic characteristics. The NIH Common Fund Gabriella Miller Kids First Program represents a first-in-kind national, collaborative initiative focused on large-scale clinical and genomic data sharing for childhood cancers and structural birth defects. As part of this program, the Kids First Data Resource Center (DRC) is charged with empowering collaborative discovery across Kids First datasets. Through newly developed platforms and cloud-based resources, researchers will be able to rapidly and interactively access standardized and harmonized clinical and genomic data. A better understanding of common developmental programs could spur advancements in prevention, detection, and therapeutics that will improve the outcomes of affected children and families. Approximately 8, 000 patient samples were available at the launch of the Kids First DRC portal including a data cohort of more than 2000 pediatric brain tumor WGS/RNAseq provided by the Children's Brain Tumor Tissue Consortium (CBTTC) and the Pacific Pediatric Neuro-Oncology Consortium (PNOC). More than 25, 000 WGS are expected to be processed by 2019, making the DRC platform one of the largest pediatric data resources across childhood diseases. The combination of harmonized genomic and clinical data across pediatric cancers and structural birth defect provides a key foundation for exploring and developing new methods to better understand the relationships between germline variants, cancer risk, and associated treatments and outcomes across cancers and especially within pediatric brain tumors.